Epidemiology, clinical picture and long‐term outcomes of FIP1L1‐PDGFRA‐positive myeloid neoplasm with eosinophilia: Data from 151 patients. Issue 11 (19th September 2020) - Rohmer, Julien; Couteau‐Chardon, Amélie; Trichereau, Julie; Panel, Kewin; Gesquiere, Cyrielle; Ben Abdelali, Raouf; Bidet, Audrey; Bladé, Jean‐Sébastien; Cayuela, Jean‐Michel; Cony‐Makhoul, Pascale; Cottin, Vincent; Delabesse, Eric; et al.
Abstract: FIP1L1‐PDGFRA‐positive myeloid neoplasm with eosinophilia (F/P+ MN‐eo) is a rare disease: robust epidemiological data are lacking and reported issues are scarce, of low sample‐size and limited follow‐up. Imatinib mesylate (IM) is highly efficient but no predictive factor of relapse after discontinuation has yet been identified. One hundred and fifty‐one patients with F/P+ MN‐eo (143 males; mean age at diagnosis 49 years; mean annual incidence: 0.18 case per million population) were included in this retrospective nationwide study involving all French laboratories who perform the search of F/P fusion gene (study period: 2003‐2019). The main organs involved included the spleen (44%), skin (32%), lungs (30%), heart (19%) and central nervous system (9%). Serum vitamin B12 and tryptase levels were elevated in 74/79 (94%) and 45/57 (79%) patients, respectively, and none of the 31 patients initially treated with corticosteroids achieved complete hematologic remission. All 148 (98%) IM‐treated patients achieved complete hematologic and molecular (when tested, n = 84) responses. Forty‐six patients eventually discontinued IM, among whom 20 (57%) relapsed. In multivariate analysis, time to IM initiation (continuous HR: 1, 01 [0.99‐1, 03]; P = .05) and duration of IM treatment (continuous HR: 0, 97 [0, 95‐0, 99]; P = .004) were independent factors of relapse after discontinuation of IM. After a mean follow‐up of 80 (56) months, the 1, 5‐ and 10‐year overall survival rates in IM‐treated patients were 99%, 95% and 84% respectively. In F/P+ MN‐eo, prompt initiation of IM and longer treatment durations may prevent relapses after discontinuation of IM.